Pandemic decimates grassroots sport, as one in 10 teen girls drop out - Fitzsimmons, C. (The Sydney Morning Herald, 2020)
Many teenage girls who played sport before the coronavirus pandemic are not returning this season and experts warn they might drop out permanently. A survey of 1000 girls aged 11 to 17 found 30 per cent of girls in NSW had lost interest in participating in team sport. The research was commissioned by Suncorp, a sponsor of netball, and did not cover boys.